ZIF-8 templated assembly of La3+-anchored ZnO distorted nano-hexagons as an efficient active photocatalyst for the detoxification of rhodamine B in water. (1st March 2021) - Karuppasamy, K.; Rabani, Iqra; Vikraman, Dhanasekaran; Bathula, Chinna; Theerthagiri, J.; Bose, Ranjith; Yim, Chang-Joo; Kathalingam, A.; Seo, Young-Soo; Kim, Hyun-Seok
Abstract: The use of lanthanum-anchored zinc oxide distorted hexagon (La@ZnO DH) nanoclusters as an active material for the photodegradation of rhodamine B (Rh–B) dye via hydrogen bonding, electrostatic, and π-π interactions is examined herein. The active photocatalyst is derived from porous zeolite imidazole frameworks (ZIF-8) via a combined ultrasonication and calcination process. The distorted hexagon nanocluster morphology with controlled surface area is shown to provide excellent catalytic activity, chemical stability and demarcated pore volume. In addition, the low bandgap (3.57 eV) of La@ZnO DH is shown to expand the degradation of Rh–B under irradiation of UV light as compared to the pristine ZIF-8-derived ZnO photocatalyst due to inhibited recombination of electrons and holes. The outstanding physicochemical stability and enhanced performance of La@ZnO DH could be ascribed to the synergistic interaction among La3+ particles and the ZnO nanoclusters and provide a route for their utilization as a promising catalyst for the detoxification of Rh–B. Graphical abstract: Facile La 3+ -anchored ZIF-8 derived ZnO nano-hexagons catalyst was synthesized which displays an enhanced photocatalytic performance. Image 1 Highlights: Facile La 3+ -anchored ZnO nanohexagon catalysts were prepared. It unveiled distorted hexagonal structure with better surface area. The La 3+ -anchored ZnO offered the narrow bandgap of 3.57 eV. It eliminated the color of Rh–B with a degradation percentage of 97%.